Use of nanoparticles to improve thermochemical resistance of synthetic polymer to enhanced oil recovery applications: a review - Quintero Perez, Henderson Ivan; Ruiz Cañas, Maria Carolina; Castro Garcia, Ruben Hernan; Romero Bohorquez, Arnold Rafael (CT&F - Ciencia, Tecnología y Futuro, 2020)
Partially Hydrolyzed Polyacrylamide (HPAM) is the polymer most used in chemical enhanced oil recovery (cEOR) processes and it has been implemented in several field projects worldwide. Polymer injection has shown to be an effective EOR process. However, it has not been implemented massively due to HPAM polymer's limitations, mostly related to thermal and chemical degradation caused by exposure at high temperatures and salinities (HTHS). As an alternative, a new generation of chemically stable monomers to improve the properties of HPAM has been assessed at laboratory and field conditions. However, the use of enhanced polymers is limited due to its larger molecular size, large-scale production, and higher costs. One of the alternatives proposed in the last decade to improve polymer properties is the use of nanoparticles, which due to their ultra-small size, large surface area, and highly reactive capacity, can contribute to reduce or avoid the degrading processes of HPAM polymers. Nanoparticles (NPs) can be integrated with the polymer in several ways, it being worth to highlight mixing with the polymer in aqueous solution or inclusion by grafting or chemical functionalization on the nanoparticle surface. This review focuses on hybrid nanomaterials based on SiO2 NPs and synthetic polymers with great EOR potential. The synthesis process, characterization, and the main properties for application in EOR processes, were reviewed and analyzed. Nanohybrids based on polymers and silica nanoparticles show promising results in improving viscosity and thermal stability compared to the HPAM polymer precursor. Furthermore, based on recent findings, there are great opportunities to implement polymer nanofluids in cEOR projects. This approach could be of value to optimize the technical-economic feasibility of projects by reducing the polymer concentration of using reasonable amounts of nanoparticles. However, more significant efforts are required to understand the impact of nanoparticle concentrations and injection rates to support the upscaling of this cEOR technology.